The ‘Urban Village’ versus the ‘City for Profit’: Querying NIMBY through a comparative analysis of touristification in Lisbon and Madrid - Aramayona, B.; Batel, S. (OBETS, 2022)
Southern European cities face the challenges associated with the recent emergence of the formal and informal economies of the 'Tourist City' and are the scenario for diverse social tensions. Local protests against these changes, sometimes discredited as NIMBY -Not In My Backyard- have led to conflicts with visitors and local public administrations. However, fuzzy definitions of the groups organising these protests are often found in the literature, as well as regarding the previous urban conditions for and the impacts of their actions. This paper presents a comparative analysis of the protests in the Portuguese neighbourhood of Bairro Alto (Lisbon) and the Spanish neighbourhood of La Latina (Madrid), in order to explore how moral ownership and 'belonging narratives' around places are variously put into play to legitimise and/or contest urban changes. We also reflect on the benefits and perils of building strong local identities versus the contemporary global tourism that flows into Southern European cities.